Druggable genomic landscapes of high-grade gliomas - Ghanem, Paola; Fatteh, Maria; Kamson, David Olayinka; Balan, Archana; Chang, Michael; Tao, Jessica; Blakeley, Jaishri, The Johns Hopkins Molecular Tumor Board Investigators; Canzoniero, Jenna; Grossman, Stuart A.; Marrone, Kristen; Schreck, Karisa C.; et al. (Frontiers in Medicine, 2023)
Background: Despite the putatively targetable genomic landscape of high-grade gliomas, the long-term survival benefit of genomically-tailored targeted therapies remains discouraging.Methods: Using glioblastoma (GBM) as a representative example of high-grade gliomas, we evaluated the clonal architecture and distribution of hotspot mutations in 388 GBMs from the Cancer Genome Atlas (TCGA). Mutations were matched with 54 targeted therapies, followed by 14.72 respectively) than patients whose actionable alterations were not targeted (2.83 and 4.2 months respectively). Conclusion: While multiple host, tumor and drug-related features may limit the delivery and efficacy of targeted therapies for patients with high-grade gliomas, genotypematched targeted therapies confer favorable clinical outcomes. Further studies are needed to generate more data on the impact of biochemical features of targeted therapies on their clinical efficacy for high-grade gliomas.